The Oxford guide to library research - Mann, Thomas (Oxford University Press, 2005)
The author maps out an array not just of important databases and print sources, but of several specific search techniques that can be applied profitably in any area of research. From academic resources to government documents to manuscripts in archives to business Web sites, He shows readers how best to exploit controlled subject headings, explains why browsing library shelves is still important in an online age, demonstrates how citation searching and related record searching produce results far beyond keyword inquiries, and offers practical tips on making personal contacts with knowledgeable people. Against the trendy but mistaken assumption that "everything" can be found on the Internet, Mann shows the lasting value of physical libraries and the unexpected power of traditional search mechanisms, while also providing the best overview of the new capabilities of computer indexing